Does Intra-articular Injection of the Ankle With Corticosteroids Increase the Risk of Subsequent Periprosthetic Joint Infection (PJI) Following Total Ankle Arthroplasty (TAA)? If So, How Long After a Prior Intra-articular Injection Can TAA Be Safely Performed?. (July 2019) - Uçkay, Ilker; Hirose, Christopher B.; Assal, Mathieu
Recommendation: Every intra-articular injection of the ankle is an invasive procedure associated with potential healthcare-associated infections, including periprosthetic joint infection (PJI) following total ankle arthroplasty (TAA). Based on the limited current literature, the ideal timing for elective TAA after corticosteroid injection for the symptomatic native ankle joint is unknown. The consensus workgroup recommends that at least 3 months pass after corticosteroid injection and prior to performing TAA. Level of Evidence: Limited. Delegate Vote: Agree: 92%, Disagree: 8%, Abstain: 0% (Super Majority, Strong Consensus)